2010
DOI: 10.1556/jep.8.2010.3.2
|View full text |Cite
|
Sign up to set email alerts
|

Women's voice pitch is negatively correlated with health risk factors

Abstract: Abstract. Previous studies have demonstrated that men prefer women's voices with relatively high pitch to those with low pitch, suggesting that men may use voice pitch as a cue of women's mate quality. However, evidence that voice pitch is a cue to women's long-term health is equivocal. Here we present evidence that women's average speaking voice pitch is negatively correlated with a health risk index derived from principle component analysis of various body measurements that are known to predict long-term hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
2
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 33 publications
(65 reference statements)
0
11
2
2
Order By: Relevance
“…Low pitched male voices are linked to larger body size, especially weight and height, to a particular body shape (shoulder and chest circumference, shoulder-to-hip ratio) (Evans et al, 2006), and arm strength (Puts et al, 2011). Nevertheless, a recent meta-analysis had shown that compared to other vocal parameters, voice pitch is not a reliable predictor of height in adults of the same sex (Pisanski et al, 2014) and it is a poor predictor of body weight, shape, and strength (Collins, 2000; Collins and Missing, 2003; Bruckert et al, 2006; Evans et al, 2006; Sell et al, 2010; Vukovic et al, 2010; Pisanski et al, 2016; Raine et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Low pitched male voices are linked to larger body size, especially weight and height, to a particular body shape (shoulder and chest circumference, shoulder-to-hip ratio) (Evans et al, 2006), and arm strength (Puts et al, 2011). Nevertheless, a recent meta-analysis had shown that compared to other vocal parameters, voice pitch is not a reliable predictor of height in adults of the same sex (Pisanski et al, 2014) and it is a poor predictor of body weight, shape, and strength (Collins, 2000; Collins and Missing, 2003; Bruckert et al, 2006; Evans et al, 2006; Sell et al, 2010; Vukovic et al, 2010; Pisanski et al, 2016; Raine et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…But also conditions beyond the speech production can be detected from voice samples, including Huntington's disease [76], Parkinson's disease [19], amyotrophic lateral sclerosis [74], asthma [104], Alzheimer's disease [27], and respiratory tract infections caused by the common cold and flu [20]. The sound of a person's voice may even serve as an indicator of overall fitness and long-term health [78,103].…”
Section: Speaker Pathologymentioning
confidence: 99%
“…Siihen vaikuttavat muun muassa puhujan sukupuoli, ikä, fyysinen koko, ääniluokka (esim. onko henkilö basso vai tenori, altto vai sopraano) sekä yksilölliset ja kulttuuriset ääni-ihanteet (Pegoraro-Krook, 1988;Scherer & Giles, 1979;Vucovic, Feinberg, DeBruine, Smith, & Jones, 2010). Luonnollisesti puhetilanne ja puhevoimakkuus (Harris & Weiss, 1964;Zraick, Gentry, Smith-Olinde & Gregg, 2006), tunnetila (Laukkanen, Vilkman, Alku & Oksanen, 1997;Waaramaa-Mäki-Kulmala, 2009;Williams & Stevens, 1972), terveydentila (Baken & Orliko , 2000;Nilsonne, 1987) ja muut vastaavat tekijät tuottavat puhekorkeuteen lyhyen aikavälin muutoksia.…”
Section: Johdantounclassified
“…Leinon tutkimusryhmän mukaan suomalaisten naisopiskelijoiden luennan keskimääräinen fo on ollut 194 Hz (keskihajonta 17 Hz) (Leino, Laukkanen, Ilomäki, & Mäki, 2008). Englannin kielen puhujilla on raportoitu naisten keskimääräiseksi fo:ksi luentapuheessa noin 207 Hz -217 Hz Britanniassa (Andreeva, Demenko, Möbius, Zimmerer, Jugler, & Oleskowicz-Popiel, 2014;Vucovic, Feinberg, DeBruine, Smith & Jones, 2010;Williams & Eccles, 1990) ja 210 Hz Yhdysvalloissa (Pepiot, 2014). Myöskin suomenkielen syntyperäisten puhujien on todettu nostavan puhekorkeuttaan puhuessaan englantia ( Järvinen, Laukkanen & Aaltonen, 2013).…”
Section: Pohdintaunclassified